Towards a maintainable and high efficiency neutral beam system for future fusion reactors. (2nd March 2021) - Simonin, A.; Blondel, C.; Chaibi, W.; Dechelle, C.; Drag, C.; Villedieu, E.
Abstract: Achievement of an economic fusion reactor imposes a high level of unprecedented requirements for neutral beam systems; the first one is the nuclear safety constraints which impose a prerequisite on the ease of access of all injector components to provide a preventive (and curative) maintenance by remote handling while maintaining reactor operation. In addition, the challenge is to develop high-power injectors with very high wall-plug efficiency (above 60%) that are able to operate in stable conditions over several months. There is a significant gap to bridge with respect to the present neutral beam systems, which are characterized by a low efficiency and by complex and long maintenance operations. Evidence that this injector concept does not offer adaptations to cope with the reactor requirements makes it clear that a new concept has to be addressed. An injector concept with modular sources at ground voltage is proposed. The concept makes remote maintenance of the injector components easier, where each source module can be replaced by a new one without breaking the vacuum and affecting injector conditioning. With the grounded and modular ion source, photoneutralization associated with energy recovery appears to be the best route capable of attaining the reactor requirements. This concept of a maintainable neutral beam system would provide a high heating power with a wall-plug efficiency above 70% and unprecedented features such as the capacity of producing temporal and spatial modulation of the beam power for a better control of the plasma stability. Up to now, photoneutralization feasibility studies already carried out on reduced-scale prototypes have not highlighted any showstoppers. Continuation of research and development in the years to come can pave the way towards the achievement of a first full-scale high-power cavity in the 1 MW range, and the realization of a multi-amperes (∼10 A) thin blade-like D − beam.